Nonlinear analysis of double layer grid structures - Gupta, L. M.; Harde, P. R. (Journal of Structural Engineering, 2024)
Nonlinear analysis is carried out to investigate load deformation response of the double layer grid structures. Iterativeincremental procedure based on Newton-Raphson technique has been used in the analysis. Experimental study is carried out to investigate the behavior of these grids. The experimental results are obtained and compared with analytical results. These results provide information to investigate the behavior of critical members in these structures.